Is There a Relationship Between the Anxiety Levels of the Pregnants in Natal and Postnatal Periods and Their Body Mass Index? Is There a Relationship Between the Anxiety Levels of the Pregnants in Natal and Postnatal Periods and Their Body Mass Index? - Hamide Zengin; Öznur Tiryaki; Sinem Yanlızoğlu Çaka; Nursan Çınar (Dokuz Eylul University, 2021)
Background: Pregnancy is one of the most important variables of women's life, causing psychological, biological and emotional changes. Objective: This study was carried out to determine the effect of pre-pregnancy body mass indexes (BMI) of pregnant women on their natal and postnatal anxiety levels. Methods: This descriptive and cross-sectional study was carried out in the gynecology and obstetrics clinic of a university hospital between 15 April and 15 May 2019. A total of 438 pregnant women who met the inclusion criteria and volunteered to participate in the study constituted the sample of the study. The data obtained using the questionnaire form consisting of 25 questions containing the introductory information of the pregnant women prepared by the researchers, and the 'Concerns About perinatal and postnatal periods Scale' were evaluated using the SPSS 22.0 statistical program. Number, percentage distribution, mean, standard deviation and Pearson correlation analysis were used in the analysis of data. Results: It was determined that the average age of 438 pregnant women participating in the study was 28.95 ± 5.39, the mean BMI before pregnancy was 24.07 ± 4.19 and the mean of the gestational week was 31.59 ± 8.90. In this study, it was concluded that the relationship between BMI before pregnancy and the "Anxiety of Inability to Receive Support from Their Husband After Birth" sub-dimension was statistically significant and the level of anxiety decreased as the BMI increased (p < .05). Conclusion: It has been determined that as pre-pregnancy BMI increases in expectant mother, the anxiety of not getting support from the spouse after birth decreases from the sub-dimensions of the Anxiety Regarding the Birth and Postpartum Period. There was no significant relationship between the other sub-dimensions of the scale and BMI. It suggested that the increase in weight gain may cause the pregnant women to need more support and this support may be provided by their spouses starting from the pregnancy period, which may have reduced postpartum fear.